ANALISIS LAJU PERTUMBUHAN DAN STRUKTUR EKONOMI KABUPATEN SRAGEN - Lilis Anisah (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2019)
The analysis of economic growth rate and structure in a region will be useful to determine the leading and potential industrial categories. The data used in this study are taken from the Statistics Agency (BPS) including economic growth rate and structure data at 2010 to 2017 in both Sragen Regency and Central Java. The analysis method used are LQ and Klassen Typology. The result of the LQ analysis show that the leading industrial categories in Sragen Regency cover A, B, D, E, G, the join of M and N, P category, then the join of R, S, U and T categories. The result of the Klassen Typology analysis state that Sragen Regency is a potential area to grow and develop economically.